Integrated spatial and transport development along European corridors. A look through the lens of stakeholder cooperation. - Braun, Cecilia; Peric, Ana (My University, 2017)
Internationale Transportkorridore sind für eine nachhaltige Mobilität von Gütern und Menschen weltweit von großer Bedeutung. Die europäischen Verkehrskorridore haben eine lange Tradition als Rückgrat des territorialen Zusammenhalts zwischen den Mitgliedstaaten der Europäischen Union. Die Arbeit beleuchtet zwei wichtige Verkehrsknotenpunkte, den Binnenhafen von Basel und den Hauptbahnhof von Belgrad. Die Verfasser kommen zu dem Schluss, dass eine bessere Zusammenarbeit der jeweils lokalen Interessengruppen dazu beiträgt, administrative Hindernisse zu überwinden und eine integrierte Entwicklung auf lokaler Ebene zu verbessern, was dann auch auf die regionale und transnationale Zusammenarbeit zu übertragen sei.

International transport corridors are becoming increasingly important in enhancing the sustainable mobility of goods and people around the world. In Europe, such a mobility issue has a much deeper meaning. Namely, European transport corridors have a long tradition in constituting the backbone of territorial cohesion among the member-states of the European Union. Thus, European integration strongly depends not only on multilateral coordination of trade and transport flows, but also on the cooperation-building projects aimed at achieving integrated spatial and transport development, most easily perceivable at the local level, i.e. in the hot-spots places with major spatial implications of transport infrastructure development. However, such an integrated approach is difficult to achieve. On the one hand, the impact of globalisation on urban development poses a threat to infrastructure investments in adjacent urban regions. On the other hand, the differences in dealing with large infrastructural and spatial development projects among various states, legal and administrative families, and finally, planning cultures also affect the transparency and inclusion of all the relevant aspects. For example, the ongoing transformation of former transport areas (railway nodes, harbours and airports) situated along the waterfronts into new urban centres is only one of many spatial conflicts between transport and urban functions. Therefore, multi-level strategic planning strategies to minimise the risks of spatial conflicts are needed. By reflecting on the findings of two bottom-up initiatives aimed at improving the cooperation among stakeholders along two European transport corridors - Rhine- Alpine and Orient/east-Med(iterranean), the paper emphasises the importance of the transportation nodes as strategic sites for inward development. Therefore, two hot-spots are presented - inland port in Basel and railway station in Belgrade. As the cases describe quite different approaches in dealing with integrated spatial and transport development, the paper concludes that the better stakeholder cooperation help to overcome the administrative obstacles and enhance integrated development at the local level. This is surely then to be transferred to the regional and transnational levels, too.
Keywords: Verkehrsweg; Verkehrskorridor; Verkehrsentwicklung; Verkehrsknoten; Knotenpunkt; Regionalentwicklung; Stadtentwicklung; Raumnutzung; Nutzungskonflikt; Interessenvertretung; Kooperation; Integrierte Verkehrsplanung; Stakeholder; Integrierte Entwicklung